(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This paper discusses a DC micro-grid-based electric vehicle (EV) charging system, which is controversial due to the debate on renewable energy and its benefits over AC. The system consists of a sun-directed photovoltaic system (PV) with a supercapacitor (SC) and battery energy storage system (BESS). The goal is to ensure optimal microgrid bus voltage and coordinated power sharing, particularly for EV charging. The strategy considers high-quality energy for DC loading, considering various loads and weather conditions, and solar irradiance. The SC is designed to provide supply during transient periods. The proposed DC microgrid uses two techniques: conventional PID technique and Artificial Neural Network (ANN) controller "feedforward-net" for power flow regulation. SC energy control minimizes voltage variations in the DC bus. An upgraded Maximum Power Point Tracking (MPPT) algorithm based on variable step size incremental conductance (VSSIC) technique is investigated for optimal system performance. A boost DC/DC converter facilitates PV system connection to the microgrid. MATLAB/Simulink is the program that is used considering properly planned task verification of performance